Just one vote : from Jim Walding's nomination to constitutional defeat - Stewart, Ian, 1953 July 2- (University of Manitoba Press, 2009)
"Using extensive research drawn from archives, interviews, and the media, Just One Vote is a retelling of a dramatic moment in Manitoba and Canadian politics. Ian Stewart outlines the geographic, social, and political backdrop behind Jim Walding's contested party nomination and the unusual chain of events it triggered, including the fall of the government of Howard Pawley, the NDP's devastating defeat in the 1988 provincial election, and the fallout from these events on the wider Canadian political landscape. Using a counterfactual argument, Stewart traces the connections between Walding's historic vote and the eventual failure of the Manitoba government to ratify the Meech Lake Accord, illustrating how singular events and individual decisions can produce large consequences as they cascade through the political system."--Jacket.